The Position and Authority of Wali Nanggroe in the Aceh Government System - Syahwandi (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2023)
Aceh is a province located at the western tip of Indonesia, a province that is thick with Islamic law which is needed for all the people who live there. province that will be thick with customs and traditions. a province that is detached from past progress and political upheaval from the post-reform era. This research entitled "The Position and Authority of Wali Nanggroe in the Aceh Government System" has a formulation of the problem of how the position of Wali Nanggroe in the Aceh Government System is, how is the procedure for the election of Wali Nanggroe and what is the position of Wali Nanggroe in the Indonesian Government. The purpose of this research is to examine how and what are the roles of Wali Nanggroe in the government of Aceh and Indonesia and how to overcome the problems that exist in aceh aceh and find out what polemics exist in this institution. This research uses library research method or library research. The data sources used are primary data, as well as secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The data will be analyzed using descriptive methods, namely research that only describes the state of the object or event without an intention to draw general conclusions. Based on the data analysis carried out, it can be concluded that there is a need to update the Qanun regarding Wali Nanggroe which is more detailed, especially regarding the role of this institution and the procedure for its election. because the presence of this institution should be a middle ground for inter-tribal conflicts in aceh. So that Aceh remains a solid province in all aspects, be it culture, religion and humanity